Right colectomy for severe and complicated acute appendicitis: A case report (International Seven Journal of Health Research, 2024)
Introduction: Acute appendicitis is an inflammation of the vermiform appendix, a small tubular organ located in the first portion of the large intestine. It can affect people of all ages, but it is most prevalent among young people aged 10 to 20. The diagnosis of acute appendicitis is predominantly clinical. In addition, it is possible to classify appendicitis according to its evolution as complicated or uncomplicated, which allows you to assess the severity of the disease. The standard approach for complicated acute appendicitis is appendectomy.  In situations of uncomplicated appendicitis, some studies suggest antibiotic therapy as an alternative to surgical treatment, however, there are controversies in this indication, but it has been gaining strength in the latest guidelines. Objective: To demonstrate the importance of the diagnosis of acute appendicitis, as well as its classification, for a better prognosis. Methods: From a medical case that occurred at the Santa Casa da Misericórdia de Presidente Prudente, and its medical records, information was collected to carry out this report. Results: Appendectomy by videolaparoscopy is associated with a lower rate of mortality, infections, and postoperative complications when compared to open surgery. However, there are cases in which laparotomy is more indicated. It is necessary to evaluate each case individually. Conclusion: In most cases, once the patient has clinical findings suggestive of acute appendicitis, he should be referred for immediate appendectomy and should not be submitted to routine imaging tests, thus reducing the time interval between diagnosis and surgical treatment, to avoid greater chances of intraoperative and postoperative complications.